English Foreign Language (EFL) Learners’ Perceptions Toward the Use of Mobile-Assisted Language Learning Applications in Learning English Language Skills - Musdizal Musdizal; Suhaimi Suhaimi (Journal of English Language and Education, 2026)
Technology plays an important role in supporting students’ English skill development. This study aims to investigate EFL students’ perceptions of Mobile-Assisted Language Learning (MALL) in improving English skills and to examine whether these perceptions differ by gender. Previous studies have widely explored EFL learners’ attitudes toward technology-assisted English learning. However, many studies discuss learners’ perceptions in general and pay limited attention to MALL or gender-based comparisons. Findings on gender differences also remain inconsistent. Some studies report differences in attitudes and technology use, while others find no significant variation. This inconsistency leaves gender’s role in MALL perceptions unclear. Moreover, few mixed-methods studies combine quantitative and qualitative data to explain how gender may or may not influence students’ perceptions of MALL. To address these gaps, this study employed an explanatory mixed-methods design. Quantitative data were collected from 72 students using Davis’s (1993) technology integration questionnaire and analyzed descriptively. Qualitative data were obtained through semi-structured interviews with ten participants and examined using thematic analysis. The survey results showed that students had generally positive perceptions of MALL, especially in terms of usefulness and ease of use. The findings also indicated no significant differences between male and female students. Interview results supported these findings by showing that MALL helped students understand learning materials and develop their English skills. Overall, this study suggests that MALL can serve as a practical technology-based medium in English instruction. It also provides lecturers with useful insights for increasing student engagement and supporting effective English skill development.